TEACHING ADJECTIVES THROUGH SHORT-STORIES - Harmonis, Dinda Ria; Sudarsono, Sudarsono; Rosnija, Eny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research investigated whether using short-stories as a teaching media was significant to teach students adjective. It was a pre-experimental research with one group pre-test and post-test design. There were 38 students of VIII D learning group who participated in this research. The data were collected by objective tests and analyzed using t-test and effect size formula. The research found that the null hypothesis (Ho) was rejected, while the alternative hypothesis (Ha) was accepted. The obtained t-value (8.75) was bigger than the critical value of r (1.678) by the degree of freedom 37. The effect size was categorized high since the ES value was 1.41 and bigger than 0.8. To conclude, teaching through short-stories is significant and very effective to teach adjectives to Year â€“ 8 students of â€œSMPN 21 Pontianakâ€ in Academic Year 2017/2018.Â Key Words: Short-stories, Adjective, Teaching Media